Granzyme-B Expression as a Predictor of Immune Surveillance (Correlation Study in Patient with Squamous Cell Carcinoma and Uterine Cervical Dysplasia) - Apriana, Ledisda; Udadi Sadhana; Ika Pawitra Miranti; Awal Prasetyo; Dik Puspasari (Biomedical Journal of Indonesia, 2021)
Background: The most common histologic type of cervical cancer is squamous cell carcinoma (SCC), with the risk of recurrence depending on immune surveillance with granzyme-B markers, and tumor infiltrating lymphocytes (TIL) is an immunological determinant associated with a better prognosis. Granzyme-B is produced by TIL. The study was aimed to prove the difference in expression of granzyme-B in SCC epithelial cells with cervical dysplasia precancerous lesions as a predictor of immune surveillance. Methods: Correlation analytic study with cross-sectional design on paraffin block patients with SCC and cervical epithelial dysplasia at the Anatomical Pathology Laboratory, RSUP Dr. Kariadi, Semarang, during 2018 and 2019, using granzyme-B immunohistochemistry assays, assessed TIL activation. Results: Most cases of cervical SCC were 40 years old, 50% were stage IIIB, 20% with the final condition died on observation 1 year after the initial diagnosis was made. The uterine cervical SCC group expressed granzyme-B with a mean score of 5.81Â±1.17 (p=0.001) and the dysplastic epithelial lesion group with a mean score of 6.83Â±0.95 (p=022), the Mann-Whitney test showed p value = 0.009, so that the test results are statistically significant. Conclusion: Expression of granzyme-B in dysplasia is higher than in uterine cervical SCC.